A rare case of live unruptured ovarian ectopic pregnancy - Khandhedia, Parth; Sharma, Karan; Joshi, Ashka (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Ectopic pregnancy is the implantation of embryo anywhere outside the uterus. The commonest location is fallopian tubes followed by previous scar, abdomen and ovary. Most of them terminates with rupture in first trimester and usually have an intricate diagnosis through surgery and histopathology. A lady in her early-thirties presented with brownish discharge per-vaginally with LMP 2 months ago and UPT positive 15 days ago. The scan revealed a good chorio-decidual reaction without any gestational sac in the uterus which was found live and unruptured along with the heartbeats in right adnexa. She was managed with emergency laparoscopic removal of the ectopic where the Gestational sac was not visualised in right tubes but astonishingly it was found in the right ovary. There were no complications post-operatively and patient was discharged in a stable condition. The overall increase in the incidence is admitted to IUCD, STI, ART, PID and many others. However, the actual factor remains unclear. The diagnosis is often made during surgery but histopathological confirmation is required. Spiegelberg Criteria defines the ovarian ectopic. Hence, it becomes peremptory to identify the cases early for complication prevention and the related deaths.